2002
DOI: 10.1046/j.1432-1033.2002.03003.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and application of two nucleoside triphosphate analogues, GTPγNH2 and GTPγF

Abstract: Guanosine triphosphate nucleotide analogues such as GppNHp (also named GMPPNP) or GTPγS are widely used to stabilize rapidly hydrolyzing protein‐nucleotide complexes and to investigate biochemical reaction pathways.Here we describe the chemical synthesis of guanosine 5′‐O‐(γ‐amidotriphosphate) (GTPγNH2) and a new synthesis of guanosine 5′‐O‐(γ‐fluorotriphosphate) (GTPγF). The two nucleotides were characterized using NMR spectroscopy and isothermal titration calorimetry. Chemical shift data on 31P, 19F and 1H N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Nucleotide Dependence of HA Release-A number of GTPases have been implicated in the delivery of HA from the TGN to the plasma membrane, including ARF1 and G s ␣ (42,43). To determine whether there is a requirement for GTP or GTP hydrolysis in HA release, we tested the effect of poorly hydrolyzable GTP analogs in our assay (44). Inclusion of GTP␥S in the reconstitution reaction decreased HA release in a dose-dependent manner with complete inhibition of ATP-dependent release observed at 100 M concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nucleotide Dependence of HA Release-A number of GTPases have been implicated in the delivery of HA from the TGN to the plasma membrane, including ARF1 and G s ␣ (42,43). To determine whether there is a requirement for GTP or GTP hydrolysis in HA release, we tested the effect of poorly hydrolyzable GTP analogs in our assay (44). Inclusion of GTP␥S in the reconstitution reaction decreased HA release in a dose-dependent manner with complete inhibition of ATP-dependent release observed at 100 M concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Adenosine 5′‐ O ‐fluorophosphate (F‐pA) was synthesized according to [23] and adenosine 5′‐ O ‐(γ‐fluorophosphate) (Fpp‐pA) according to procedure developed for the synthesis of GTPγF [24]. Other adenine (di)nucleotides were from Sigma, St. Louis, MO, USA.…”
Section: Methodsmentioning
confidence: 99%
“…We have sorted these arbi-trarily according to the binding partner for the protein, i.e. small molecules (physiological ligands), [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] drug/inhibitor (natural and synthetic inhibitors), 37-44 other proteins (or peptides derived thereof), nucleotides, 72-77 metal ions, 78-89 polysaccharides [90][91][92][93][94][95][96] and lipids. [97][98][99] Finally some additional miscellaneous studies reported on some surface chemistry 100,101 and protein-folding studies were published.…”
Section: Protein-ligand Interactionsmentioning
confidence: 99%